Antifungal activity and biocompatibility assessment with molecular docking and dynamic simulations of new pyrazole derivatives - Basma T. Abd-Elhalim; Ghada G. El-Bana; Ahmed F. El-Sayed; Ghada E. Abdel-Ghani (BMC Biotechnology, 2025)
Abstract Background Because of their many bioactivities, which include psychoanalytic, antifungal, antihypertensive, anti-inflammatory, and antiviral properties, pyrazoles and their derivatives are attracting interest in pharmacology and medicine, the pressing need for novel fungicides is increased for lessened by the growing microbiological resistance of illnesses to recognized antibiotics. Objective The current work validates the results and pyrazole binding sites as potent antifungals by investigating many pyrazole derivatives as antifungal agents. The biocompatibility was assessed using an HFB4 normal human skin cell line. Methods The biocompatibility was evaluated using an HFB4 normal human skin cell line and the findings of pyrazole binding sites were confirmed using molecular docking. The antifungal investigation was against 4 fungal pathogens: Aspergillus flavus ATCC 9643, A. niger ATCC 11414, Rhizopus oryzae ATCC 96382, and Penicillium chrysogenum ATCC 10106. Results Among 20 different Pyrazole derivatives, Pyrazole 3b is the most effective compound against A. niger ATCC 11414 and A. flavus ATCC 9643 with IZDs and AIs of 32.0 mm (1.10) and 30.0 mm (1.0), respectively. Followed by compound 10b scored 28 and 20 mm for A. niger and P. chrysogenum ATCC 10106, respectively. While R. oryzae ATCC 96382 exhibited resistance with all pyrazole compounds. The study found that pyrazole 3b showed 100% antifungal activity between 1000 and 500 μg/ml, 50% at doses of 250 μg/ml, and no antifungal action at a dose of 125 μg/ml against the studied pathogenic fungal strains. The biocompatibility investigation showed that the 3b compound was completely safe with no IC50 dose obtained. The effectiveness of several pyrazole compounds against fungal targets was confirmed through molecular docking studies. The results highlighted that compounds 3b, 3g, 3h, 10b, 7, and 12 displayed strong binding energies, effectively engaging with the active sites of key proteins in various fungi such as FDC1 in A. niger, uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) in A. flavus, and Adenosine 5′-phosphosulfate kinase in P. chrysogenum. These interactions encompassed diverse molecular bonding types, suggesting these compounds’ potential to hinder enzyme activity and demonstrate notable antifungal properties. Additionally, the computational ADMET “Absorption–distribution–metabolism–excretion–toxicity” analysis of these compounds revealed adherence to Lipinski’s rules, indicating favorable physicochemical characteristics. The molecular dynamic simulations of Adenosine 5’-phosphosulfate kinase in P. chrysogenum, UDP-N-acetylglucosamine in A. flavus, and FDC1 in A. niger with 10b also demonstrated the formation of stable complexes with favorable values of Root Mean Square Deviation (RMSD), Root Mean Square Fluctuation (RMSF), Solvent Accessible Surface Area (SASA), and Radius of Gyration (Rg). These findings support the compounds’ potential in ongoing therapeutic development projects. Conclusion The study found that pyrazole 3b was the most effective antifungal agent. The compounds’ strong binding energies with fungi proteins suggest potential drug development.